2017
DOI: 10.1002/ajh.24855
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of chronic organ damage in adult sickle cell patients: A seven‐year follow‐up study

Abstract: Organ damage in sickle cell disease (SCD) is a crucial determinant for disease severity and prognosis. In a previous study, we analyzed the prevalence of SCD-related organ damage and complications in adult sickle cell patients. We now describe a seven-year follow-up of this cohort.All patients from the primary analysis in 2006 (n = 104), were included for follow-up. Patients were screened for SCD-related organ damage and complications (microalbuminuria, renal failure, elevated tricuspid regurgitation flow velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
3
21
0
1
Order By: Relevance
“…LDH was associated with TRV elevation in children with SCD if genotype or treatment exposure was not accounted. TRV elevation increases over time in adults with SCD; therefore, prospective serial evaluations are necessary in children with SCD to better understand the longitudinal changes in hemoglobin that may occur with TRV and how it relates to disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…LDH was associated with TRV elevation in children with SCD if genotype or treatment exposure was not accounted. TRV elevation increases over time in adults with SCD; therefore, prospective serial evaluations are necessary in children with SCD to better understand the longitudinal changes in hemoglobin that may occur with TRV and how it relates to disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular filtration rate progressively declines with age, with an annual rate of decline of kidney function of 1·27 ± 1·97 ml/min/1·73 m 2 reported in African‐American adults (Young et al , ). Multiple previous studies suggest that kidney function progressively declines in SCD (Gosmanova et al , ; Asnani et al , ; van Tuijn et al , ; Xu et al , ; Derebail et al , ). In a 25‐year prospective longitudinal demographic and clinical cohort study, 31 out of 725 patients with HbSS (4·2%) and 5 out of 209 patients with HbSC disease (2·4%) developed chronic renal failure (Powars et al , ).…”
Section: Discussionmentioning
confidence: 94%
“…A retrospective, single centre study of 98 SCD patients found that the prevalence of CKD, defined according to the 2012 KDIGO recommendations, increased from 28·6% to 41·8% after a mean follow‐up of 5 years (Gosmanova et al , ). In a more recent single‐centre, prospective study of 104 patients in the Netherlands, the prevalence of renal failure increased from 6·7% to 23·4% after 7 years of follow‐up (van Tuijn et al , ). Although these studies assessed the progression of CKD, they did not evaluate rapid decline in kidney function and its association with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This survival increase is primarily due to mandatory newborn screening, infection prevention with penicillin prophylaxis and pneumococcal vaccination, improved supportive care, and increased use of disease‐modifying therapies, such as hydroxyurea and chronic erythrocyte transfusions . However, accumulation of end‐organ damage to the heart, lungs, brain, kidneys, and bones continues to occur . This organ damage manifests in young adults with higher rates of acute health utilization, emergency room reliance, and hospitalization .…”
Section: Introductionmentioning
confidence: 99%